Guideline concordance of bisphosphonates used for osteoporosis in a University Hospital, Thailand - Supalerk Anusathitwattana (2022)
Bisphosphonates (BPs) are recommended as the first-line medication for osteoporosis mostly occurs in postmenopausal women and elderly men. This study was conducted to investigate (i) the percentage of prescribing BPs concordant to the Thai Osteoporosis Foundation 2010 (TOPF 2010) guideline, (ii) the cause of prescribing BPs non-concordant to the TOPF 2010 guideline, (iii) the prevalence of osteoporotic fracture, (iv) the factors related to osteoporotic fracture, and (v) the loss of medication cost determined from group of patients who received BPs non-concordant to the TOPF 2010 guideline. A nested case-control study was performed in all patients of Ramathibodi Hospital who consumed BPs during January and December 2012. One thousand patients were eventually recruited. Of these, 784 patients (78.4%) received BPs concordant to the TOPF 2010 guideline and 216 patients (21.6%) did not. The major cause of using BPs non-concordant to the TOPF 2010 guideline was low bone mass without clinical risk factors (104 of 216 patients, 48.1%). Prevalence of osteoporotic fractures was 2.9%. Age (men ≥70 years and women ≥65 years) showed significant factor related to osteoporotic fracture with OR 1.0658 (95%Cl: 1.0248-1.1084; P=0.0015). Loss of medication cost in the group of patients who received BPs non-concordant to the TOPF 2010 guidelines was 4,261,488 THB/year. In conclusion, the concordance of BPs with TOPF 2010 guideline was 3.6 times higher than the non-concordance (78.4% concordance and 21.6% non-concordance).